Green Synthesized Nanoparticles as a Novel Alternative Paradigm for the Therapeutic Management of Intracellular Protozoa - Raghda Mahmood Hamad; Mohammed Mohsen Sharqat Ali Al-Jumaili (American Journal of Biology and Natural Sciences, 2026)
Intracellular parasitic protozoa such as Toxoplasma gondii, Leishmania spp., and Plasmodium falciparum continue to be a huge global public health and socio-economic problem. Modern frontline chemotherapy [remains] largely dependent on drugs with a history of development decades ago, including pyrimethamine, sulfadiazine, and antimonials. However, alarming rates of drug resistance, extreme systemic toxicities, and poor bioavailability have increasingly compromised these standard regimens, in addition to their inability to safely eradicate latent encysted tissue stages. Applied parasitology has been used for many years however, more recently the interface between green nanotechnology and applied parasitology has presented a novel, innovative alternative. This update review elaborates current advances during the past five years (2022–2026) on the use of biogenic metal and metal oxide nanoparticles (NPs), in particular Ag, Au, Se, ZnO and CuO mediated with various bioactive plant extracts as innovative new anti parasitic platforms. We present a rigorous assessment of their preclinical biomedicinal efficacy against both tachyzoite and bradyzoite stages, elucidate their multi-targeted intracellular mechanisms of action (ROS mediated apoptosis, membrane disruption, downregulation of key virulence genes) and identify current physiological bottlenecks that may limit clinical translation. Finally, we discuss bioengineering strategies that will be required to design optimized, targeted, and non-toxic nanoscale molecular formulations for biomedical applications in the future